2019
DOI: 10.26493/978-961-7055-43-6
|View full text |Cite
|
Sign up to set email alerts
|

Women, Migrations and Health

Abstract: Several topical issues arising from the contemporary migrant context, at both regional and global levels, are addressed in the chapter. First, when it comes to the sphere of the European Union, the emphasis is on the issues of integration in the migrant context, as well as the security situation. Women have often been heavily involved in the survival of their families and communities, but today the 'feminisation of migration' and 'feminisation of survival' processes are very evident. These two phrases highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 102 publications
(150 reference statements)
0
1
0
Order By: Relevance
“…It has also been found that observing the local and cultural context to identify novel factors will strengthen the knowledge and benefits the clients and stakeholders (46,162,178). Healthcare practices that are culturally sensitive were found to improve awareness of falls, clients' satisfaction, and other patient outcomes (178)(179)(180)(181). Therefore, it is hoped that this scoping review provides an insight for future research to consider both elements when conducting studies on falls and stroke.…”
Section: Establishing a Comprehensive Framework To Guide Stroke And Fmentioning
confidence: 92%
“…It has also been found that observing the local and cultural context to identify novel factors will strengthen the knowledge and benefits the clients and stakeholders (46,162,178). Healthcare practices that are culturally sensitive were found to improve awareness of falls, clients' satisfaction, and other patient outcomes (178)(179)(180)(181). Therefore, it is hoped that this scoping review provides an insight for future research to consider both elements when conducting studies on falls and stroke.…”
Section: Establishing a Comprehensive Framework To Guide Stroke And Fmentioning
confidence: 92%